Factors Associated with Morbidity Among Hajj Pilgrims in Medan City in 2024 - Armis Sibuea, Nerry; S. Otniel Ketaren; Jasmen Manurung; Donal Nababan; Henny Arwina Bangun (JURNAL KESMAS DAN GIZI (JKG), 2025)
Indonesia sends hundreds of thousands of Hajj pilgrims every year. Many pilgrims depart at an elderly age due to limited quotas and long waiting periods. This situation contributes to the recurrence of health problems among Hajj pilgrims. The purpose of this study was to analyze the factors associated with morbidity among Hajj pilgrims from Medan City in 2024. This research employed a descriptive-analytic approach with a cross-sectional study design. The study was conducted at the Health Quarantine Office of North Sumatra Province from August 2024 to February 2025. The results showed significant associations between age (p-value 0.000), medical history (p-value 0.000), istithaah (physical/medical eligibility) status (p-value 0.001), and health risk status (p-value 0.000) with morbidity among Hajj pilgrims in Medan City. The most dominant factor influencing morbidity was high-risk health status, with an Exp(B) value of 19.745 and a p-value of 0.000. It is recommended that the Ministry of Religious Affairs establish a maximum age limit for Hajj registration, taking into account the waiting period until the Hajj is performed, to help ensure pilgrims are not too old to perform the pilgrimage. Additionally, it is advised that the Medan City Port Health Office (BKK) be more proactive and responsive in managing high-risk prospective pilgrims by providing training for healthcare workers.